2016
DOI: 10.1115/1.4033211
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Effect on Mixed Convection in Lid-Driven Trapezoidal Cavities Filled With a Cu–Water Nanofluid With an Aiding or Opposing Side Wall

Abstract: The present study investigates mixed convection inside a Cu–water nanofluid filled trapezoidal cavity under the effect of a constant magnetic field. The mixed convection is achieved by the action of lid-driving of the right hot inclined side wall in the aiding or the opposing direction. The left inclined side wall is fixed and kept isothermal at a cold temperature. The horizontal top and bottom walls are fixed and thermally insulated. The magnetic field is imposed horizontally. The problem is formulated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…They found that side angles have a significant impact on the heat transfer when forced convection dominates; whereas a negligible effect during natural convection mode is observed. In another study, Chamkha and Ismael (2016) studied the dampening effect of magnetic fields on thermal behavior. Mixed convection under the double-diffusion of air (Pr = 0.7) filled right-angled trapezoidal enclosure (with inward side angles of 45º and 60º) heated partially has been investigated by Ababaei et al (2018) and observed that heat and mass transfer were significantly affected by the side angle as well as flow control parameters.…”
Section: Introductionmentioning
confidence: 99%
“…They found that side angles have a significant impact on the heat transfer when forced convection dominates; whereas a negligible effect during natural convection mode is observed. In another study, Chamkha and Ismael (2016) studied the dampening effect of magnetic fields on thermal behavior. Mixed convection under the double-diffusion of air (Pr = 0.7) filled right-angled trapezoidal enclosure (with inward side angles of 45º and 60º) heated partially has been investigated by Ababaei et al (2018) and observed that heat and mass transfer were significantly affected by the side angle as well as flow control parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It did note that the features of heat transfer and fluid flow inside the cavities were entirely conditional on Reynolds and Grashof numbers. Chamkha and Ismael 13 explored the mixed convection of the right heat-inclined sidewall within a lid-driven nanofluid-filled trapezoidal cavity with the impact of the uniform magnetic field. The authors showed that the Nusselt number’s action varies from the Richardson number associated with the lid’s direction.…”
Section: Introductionmentioning
confidence: 99%
“…For controlling and enhancement of the convection heat transfer, a liddriven wall is used [7][8][9][10][11][12][13][14] and a rotating cylinder used inside the enclosures [15]. When using Rayleigh number 1-1400 show the influence of the rotating cylinder to increasing thermal transfer by Lewis [16].…”
Section: Introductionmentioning
confidence: 99%